Factors Predicting Prejudice toward Syrian Immigrants - Gülüm, Zeynep; Gölge, Zeynep Belma (The Bulletin of Legal Medicine, 2024)
Objective: The current study aims to reveal the factors that predict the prejudice of citizens of the Republic of Türkiye toward Syrian immigrants.Methods: The sample consists of 461 people aged 18/over from different social segments of Istanbul and Hatay provinces. The level of predictive power of the social dominance orientation, the group identification, the integrated threat theory and the intergroup contact scales on prejudice toward immigrants was determined by using hierarchical regression analysis.Results: Upon evaluating the statistical data from the scales, it was found that the mean perception of realistic threat in the Istanbul sample (x̅=41.28) was significantly lower than in the Hatay sample (x̅=45.06), with a statistically significant difference [t(458)=4.713, p
Keywords: Syrian immigrants; Prejudice toward immigrants; Discrimination; Hate crime